Additional file 2 of Comparative genomics of the coconut crab and other decapod crustaceans: exploring the molecular basis of terrestrial adaptation - Werner Pieter Veldsman (10733028); Ka Yan Ma (9348645); Jerome Ho Lam Hui (10733031); Ting Fung Chan (8826122); J. Antonio Baeza (9012707); Jing Qin (41397); Ka Hou Chu (10274112) (2021)
Additional file 2: Table S2. tRNA amino acid anti-codon bias.